IMPLEMENTATION OF SOCIAL SECURITY GUARANTEE (BPJS) PROGRAM IN THE REGIONAL GENERAL HOSPITAL OF BARRU REGENCY - Suraiyati Hasan (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal